Evaluation of augmented reality cues to improve the safety of left-turn maneuvers in a connected environment: A driving simulator study. (December 2020) - Calvi, Alessandro; D'Amico, Fabrizio; Ferrante, Chiara; Bianchini Ciampoli, Luca
Highlights: Crash data show that left-turns are quite dangerous maneuvers. Augmented Reality (AR) could enable future systems to detect dangers earlier. AR warnings increase the number of safe left-turns of connected vehicles. Delays at intersection decreases using AR warnings. No significant differences are observed among different AR warning configurations. Abstract: Left-turns are some of the most dangerous maneuvers drivers face as they involve a complex decision-making process. Indeed, drivers must wait for an adequate gap in oncoming traffic to safely complete a left-turn maneuver. In this context, incorrectly assessed gaps can lead to severe crashes and severe traffic delays at intersections. This study tests the potential of Augmented Reality (AR) technology, built into connected vehicle technology, to improve the safety of left-turn maneuvers of connected vehicles by adding visual virtual information to the driver. To achieve this goal, a driving simulator study was carried out. The effectiveness of the system was tested, and the ability of young drivers to detect adequate gaps between vehicles in the opposite lane (with right of way) to safely turn left was assessed with and without AR warnings at a two-way stop-controlled intersection under a connected vehicles environment. In the scenario projected on the simulation screen, three different virtual warnings were displayed and tested: a green/red traffic light, which informs the driver of the availability of an appropriate gap between opposing vehicles; a traffic light with a timer showing the number of seconds available to safely perform the left-turn maneuver; a traffic light with an additionally activated audio warning system. Significant positive effects of AR warnings on driving performance and traffic safety were observed: the number of safe left-turns increased and the delays at the intersection decreased. In addition, AR signaling improved driving behavior both during the waiting time, with many more drivers waiting for the gap in front of the stop line to avoid disrupting oncoming traffic, and turning movement, reducing the average time it took to complete the left-turn maneuver. This study confirmed the great potential of AR and connected vehicle technologies to improve general safety conditions on the road network, especially under risky situations and difficult maneuvers.